2007
DOI: 10.1002/jbm.b.30815
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sulfate–carboxymethylcellulose bone graft binder: Histologic and morphometric evaluation in a critical size defect

Abstract: Calcium sulfate (CS) is widely used as a bone graft binder and expander. Recent reports indicate that carboxymethylcellulose (CMC) can improve the clinical properties of CS when used as binder for particulate bone grafts; however, limited information is available on the effects of CMC on bone regeneration. The purpose of this study was to evaluate the histologic and morphometric characteristics of bone formation in calvarial defects grafted with a CS-based putty containing 10% CMC in combination with allogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 38 publications
0
44
0
2
Order By: Relevance
“…CMC and HPMC are considered suitable carriers based on evidence that both substances support the osteoinductive capacities of BMP‐25, 21–27 and BMP‐7,6–10, 28 as well as the osteoconductive properties of bone substitutes 29. However, whether CMC or HPMC can control the formation or the activity of osteoclasts and osteoblasts is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CMC and HPMC are considered suitable carriers based on evidence that both substances support the osteoinductive capacities of BMP‐25, 21–27 and BMP‐7,6–10, 28 as well as the osteoconductive properties of bone substitutes 29. However, whether CMC or HPMC can control the formation or the activity of osteoclasts and osteoblasts is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast to studies that have previously compared use of CMC in vivo and as a carrier for bone graft materials. A histological study by Reynolds et al () investigated the use of CMC as a binder in the development of an injectable calcium sulfate putty and reported that CMC was well tolerated by tissue and supported bone formation in a critical sized rat calvarial model. Results showed comparable levels of new bone formation when compared with CS graft alone.…”
Section: Discussionmentioning
confidence: 99%
“…When used as a carrier for bone morphogenetic protein-2, bone formation was enhanced in rat and non-human primate calvarial defect models [11,21]. Reynolds et al [20] proposed that CMC can serve as a thixotrophic agent and function to stabilize polymers and drug delivery vehicles. Cho et al [5] reported that a calcium sulfate-based putty containing CMC promoted early bony consolidation in distraction osteogenesis.…”
Section: Discussionmentioning
confidence: 99%